Quality certifications for nonprofits, charitable giving, and donor's trust: experimental evidence - Maja Adena; Jeyhun Alizade; Frauke Bohner; Julian Harke; Fabio Mesters (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
In an experiment, we test the impact of quality certificates on donations to a charity. Compared to the control group, participants presented with a quality certificate chose higher donations by around 10% and reported higher trust towards the same charity. The choice of donation values over time shows strong persistence such that the difference between the two groups remained even after all participants were informed about the certificate. Since the initially uninformed donors did not adjust their donations sufficiently upwards, we conclude that quality certification is less likely to affect giving of existing donors. Finally, we find no significant effect of information about certificate fees.
https://doi.org/10.7802/1.2121
Keywords: D64; C99; D81; 330; non-profit certification; charitable giving; experiment; trust